Three-dimensional modeling of creep deformation in magnesium reduction retorts. (November 2019) - Shahheidari, M.; Sadeghi, A.; Sadeghi, M.H.
Abstract: Metallic magnesium is produced through a reduction reaction inside thick-walled tubes called retorts. Retorts operate at 1200 °C with an internal vacuum that causes high temperature creep deformation and short lifespan. This paper predicts retort creep deformation via three-dimensional (3D) finite element simulation using creep model constants obtained by experimental tests. Simulation results were verified by comparing the ovality of cross-sections along the axial length of an experimentally failed retort with <10% error. The discrepancies are resulted from the crack formation by creep at the grain boundaries and further inside the enlarged grains accelerated by precipitation and internal oxidation. Results spotlighted the detrimental effect of a temperature gradient at the retort's cool end on localized deformation along its length. Optimization results indicated that retort wall thickness exerts more significant effect compared to the retort diameter on lifespan and economic performance (three times). Retort dimensions of 325 mm inner diameter and 35 mm wall thickness represent the most economical geometry. Highlights: A 3D FE model was developed to simulate creep deformation of Mg reduction retorts Temperature gradient at the condenser localizes deformation and reduces lifespan Employing the validated model, effects of inner diameter and thickness are studied Retort geometry is optimized to minimize the share of retort cost per kg yield of Mg The most economical geometry is represented by a 325 mm ID and 35 mm thick retort